Patterns in assignment submission times: Analysis of factors contributing to undergraduate students’ commitment to core-curriculum related course - Ahmad Bisyri Husin Musawi Maliki; Abd Majid Mohd Isa; Mohamad Nizam Nazarudin; Mohamad Razali Abdullah; Siti Musliha Mat-Rasid; Rabiu Muazu Musa (Heliyon, 2024)
Co-curricular activities equip students with essential skills and knowledge for personal and professional growth. Despite their importance, many students exert minimal effort to complete the assigned tasks. Instructors perceive that the lack of emphasis on final exams in co-curricular subjects reduces student effort and commitment. Moreover, poor time management and lack of effort in completing tasks have increased across various subjects in recent years. Therefore, it is important to investigate the factors that contribute to student commitment towards co-curricular subjects. In this study, the submission status of 339 tasks was retrieved from the student learning system to measure student commitment based on whether tasks were submitted on time, delayed, or not submitted. A chi-square test f was used to investigate the relationship between students’ demographic characteristics and their commitment. The findings revealed a significant association between student commitment and the type of task given (p < 0.001). Students were more likely to submit presentations on time compared to written assignments. Projects were more likely to be delayed, while written assignments had a high frequency of no submission. Age was a significant predictor of commitment (p < 0.05), with students over 20 more likely to submit on time and students under 20 more likely to ignore submission. Gender was also a significant predictor of commitment (p < 0.001), with female students having a higher percentage and frequency of on-time submissions while male students having a higher number of no submissions. However, no significant association was found between the study year and commitment (p > 0.05), indicating that the year of the study could not determine the level of commitment to the course. Overall, these findings could be used to guide the preparation of tasks and assignments in co-curricular subjects to enhance student commitment and holistic development.